Recent advance of the hepatitis B virus inhibitors: a medicinal chemistry overview. (April 2015) - Jia, Haiyong; Rai, Diwakar; Zhan, Peng; Chen, Xuwang; Jiang, Xuemei; Liu, Xinyong
Hepatitis B Virus (HBV) is one of the most prevalent viral infections of human worldwide. The therapies are limited in the clinical context because of negative side effects of interferons and the development of viral resistance to the nucleoside/nucleotide inhibitors. In this review, we summarize the recent advances in design and development of potent anti-HBV inhibitors from natural sources and synthetic compounds, targeting different steps in the life cycle of HBV. We attempt to emphasize the major structural modifications, mechanisms of action and computer-aided docking analysis of novel potent inhibitors that need to be addressed in the future to design potent anti-HBV molecules.